Reviewing the Modeling Aspects and Practices of Shallow Geothermal Energy Systems - Christodoulides, Paul; Vieira, Ana; Lenart, Stanislav; Maranha, João Ribas; Vidmar, Gregor; Popov, Rumen; Georgiev, Aleksandar G.; Aresti, Lazaros; Florides, Georgios A. (My University, 2020)
Shallow geothermal energy systems (SGES) may take different forms and have recently taken considerable attention due to energy geo-structures (EGS) resulting from the integration of heat exchange elements in geotechnical structures. Still, there is a lack of systematic design guidelines of SGES. Hence, in order to contribute towards that direction, the current study aims at reviewing the available SGES modeling options along with their various aspects and practices. This is done by first presenting the main analytical and numerical models and methods related to the thermal behavior of SGES. Then, the most important supplementary factors affecting such modeling are discussed. These include: (i) the boundary conditions, in the form of temperature variation or heat flow, that majorly affect the predicted thermal behavior of SGES; (ii) the spatial dimensions that may be crucial when relaxing the infinite length assumption for short heat exchangers such as energy piles (EP); (iii) the determination of SGES parameters that may need employing specific techniques to overcome practical difficulties; (iv) a short-term vs. long-term analysis depending on the thermal storage characteristics of GHE of different sizes; (v) the influence of groundwater that can have a moderating effect on fluid temperatures in both heating and cooling modes. Subsequently, thermo-mechanical interactions modeling issues are addressed that may be crucial in EGS that exhibit a dual functioning of heat exchangers and structural elements. Finally, a quite lengthy overview of the main software tools related to thermal and thermo-hydro-mechanical analysis of SGES that may be useful for practical applications is given. A unified software package incorporating all related features of all SGES may be a future aim.
Keywords: Energy geo-structures; Modeling; Shallow geothermal energy systems; Software tools; Thermal analysis; Thermo-hydro-mechanical